الحوار الديني في كتاب "الجواب الصحيح" (ش تشن تشنغ دا) لوانغ داى يو: دراسة تحليلية ونقدية - يانغ، جينغ (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Sheikh Wang Dai-yu (王岱舆) who lived in the seventeenth century of the Gregorian era is the earliest Chinese Muslim scholar whose works on the explication of the teachings of Islam have reached us. The present research is an attempt at studying and analyzing the dialogues and controversies contained in his book entitled True Answers of the Very Real (XI ZHEN ZHENG DA). Those dialogues and controversies took place between Sheikh Wang Dai-yü and groups of Buddhists, Daoists, Confucians and some Muslims on different intellectual and creedal issues, such as belief in God, the prophets and the hereafter. The researcher has classified the dialogues according to the different issues and subjects dealt with a view to identify the methodology used in dealing with them. The researcher has also analyzed some of the discussions in those dialogues. To the researcher's knowledge, this is the first work done in Arabic on Sheikh Wang's book True Answers. It thus brings to light one important aspect of Chinese Muslim scholars' contributions in defending Islam and protecting Muslims in China from extinction. It also provides a useful methodological lesson to researchers and propagators of the Islamic message on how to engage in dialogue with the followers of other religions.